The Effect of U.S. University Students' Problematic Internet Use on Family Relationships: A Mixed-Methods Investigation. - Susan M Snyder; Wen Li; Jennifer E O'Brien; Matthew O Howard (PLoS ONE, 2015)
This is the first study to investigate how college students in the U.S. with problematic Internet use perceive the role the Internet plays within their families of origin. The sample included 27 U.S. university students who self-identified as excessive Internet users. Participants reported spending more than 25 hours a week on the Internet on non-school or non-work-related activities and reported Internet-associated health and/or psychosocial problems. This study provides descriptive statistics from participants' completion of two problematic Internet use measures (i.e., Young's Diagnostic Questionnaire and the Compulsive Internet Use Scale) and reports findings from four focus groups. Three themes emerged from the focus groups: (1) family connectedness, (2) family conflict/family disconnection, and (3) family Internet overuse. The findings of this study are a first step toward the design of effective interventions for problematic Internet use among U.S. college students and serve to inform clinical practice and health policy in this area.